Development and test of resistive superconducting fault current limiter; acting time and its recovery conditions - Baldan, Carlos A. [UNESP]; Guedes, Luciano C.; Lamas, Jerika S.; Shigue, Carlos Y.; Ruppert, Ernesto (Iop Publishing Ltd, 2014)
Resistive-type of superconducting fault current limiters (RSFCL) have been developed for medium voltage class aiming to operate at 1 MVA power capacity and short time recovery (< 2 s). A RSFCL in form of superconducting modular device was designed and constructed using 50 m-length of YBCO coated conductor tapes for operation under 1 kV / 1 kA and acting time of 0.1 s. In order to increase the acting time the RSFCL was combined with an air-core reactor in parallel to increase the fault limiting time up to 1 s. The tests determined the electrical and thermal characteristics of the combined resistive/ inductive protection unit. The combined fault current limiter reached a limiting current of 583 A, corresponding to a limiting factor of 3.3 times within an acting time of up to 1 s.